Advances in Preclinical Platforms of Loa loa for Filarial Neglected Tropical Disease Drug and Diagnostics Research - Wanji, Samuel; Chunda, Valerine Chawa; Fombad, Fanny Fri; Njouendou, Abdel Jélil; Gandjui, Narcisse Victor T.; Ritter, Manuel; Enyong, Peter A.; Mackenzie, Charles; Taylor, Mark J.; Hoerauf, Achim; Turner, Joseph D. (Frontiers in Tropical Diseases, 2021)
The tropical disease, loiasis, caused by the filarial parasite, Loa loa, has gained prominence in global public health as a cause of excess mortality and a barrier to the elimination of the related prioritized neglected tropical diseases (NTDs), lymphatic filariasis and onchocerciasis, within Central Africa. There are no effective drug cures or vaccines available to treat loiasis safely. Here we review recent advances in loiasis preclinical platform technologies, including novel in vitro culturing systems, animal models and innovations in experimental infections of the L. loa vector, Chrysops, that have facilitated access to all L. loa filarial life-cycle stages. We detail applications of these new model systems in anti-filarial drug screening, diagnostic development, immunology, and pathophysiology research. Finally, we provide an overview of how loiasis preclinical platforms may be further utilized in translational medicine applications to support the development of much needed new interventions against filarial NTDs.